1995
DOI: 10.1159/000184622
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Urinary Steroid Profiles in Children with Adrenocortical Tumors

Abstract: The excretory patterns of urinary steroids determined by capillary gas chromatography in 11 children (aged 0.8-16.5 years) with adrenocortical tumors were established. In 8 patients the predominant clinical feature was virilization, in 3 others, Cushing’s syndrome. In 5 patients (3 carcinoma, 2 adenoma) very high excretion of 3β-hydroxy-5-ene steroids was observed. In 2 others (adenomas) only moderately elevated excretion of 11β-hydroxyandrosterone was found. In 1 patient (adenoma) pregnanediol dominated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…This may be explained by relatively inefficient steroid production in ACC, manifesting with increased steroid precursors, due to a dedifferentiated and thus incomplete pattern of steroidogenic enzyme expression. This appears to be supported by some case reports and a small series analyzing steroid excretion in ACC (2124). …”
supporting
confidence: 63%
“…This may be explained by relatively inefficient steroid production in ACC, manifesting with increased steroid precursors, due to a dedifferentiated and thus incomplete pattern of steroidogenic enzyme expression. This appears to be supported by some case reports and a small series analyzing steroid excretion in ACC (2124). …”
supporting
confidence: 63%
“…While the seminal studies by Shackleton and coworkers in 1968 were conducted by means of thin-layer chromatography and direct reflectance densitometry, requiring a full week of manpower to analyze six urine specimens [1], the use of column chromatography [2][3][4][5][6] and, eventually, gas chromatography/mass spectrometry (GC-MS) [7][8][9] as well as liquid chromatography/(tandem) mass spectrometry [LC-MS(/MS)] [10] provided the speed, sensitivity, and robustness to establish test methods for blood and urine steroid analysis for clinical, forensic, and doping control purposes [11,12]. Due to the importance of unambiguous identification and determination of the target compounds, exhaustive mass spectrometric studies were conducted concerning structure elucidation and characterization of dissociation patterns of steroidal compounds using electron ionization [13] and electrospray ionization (ESI) with collision-induced dissociation (CID) [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This observation was subsequently confirmed by other small studies [100][101][102]. Urinary Δ5 steroid metabolites including 5-pregnenediol (5-PD) and 5-pregnenetriol (5-PT)degradation products of pregnenolone (Preg) and 17OHPreg are also elevated in ACC [100,[102][103][104]. One of the initial studies of serum steroids in ACC by Gröndal et al demonstrated elevated levels of Preg-S in all and of 11dF in 72% of the ACC patients (Table 1) [105].…”
Section: Adrenocortical Carcinomamentioning
confidence: 53%